Epidemiology, Seasonal Variability, and Factors Associated with Increased Mortality in Patients with Acute Appendicitis in Thailand: A Study Using Data from the National Health Security Office - Khongcharoen, Natthapon; Khiawthuam, Nattaya; Chouchuen, Pongsakorn; Surachat, Komwit; Sirichamratsakul, Kulpreeya; Sangkhathat, Surasak (PSU Medical Journal, 2024)
Objective: The study aimed to study the spatiotemporal distribution of acute appendicitis in Thailand, using a reimbursement dataset from the National Health Security Office, and also analyze for mortality and factors associated with mortality after an appendectomy. Material and Methods: The study used data mining to analyze a reimbursement data set from the Thailand National Health Security Office (NHSO), focusing on the diagnosis of acute appendicitis (K35.2-K35.9). The analysis looked for the incidence trend and seasonal variation of the incidence. The study also analyzed mortality and factors associated with the mortality. A prediction model for mortality was constructed using a decision tree. Results: During the 4 fiscal years of the study period, from October 2016 - September 2020, a total of 287,449 individuals were diagnosed with acute appendicitis, and 272,850 appendectomies were performed, which gave an annual incidence (AI) of 10.8/10,000 person-years. The peak age incidence was in the second decade of life, which had an age-specific AI of 28.4/10,000 person-years. Using a multiplicative model of time series detrending and a decomposition model and a seasonal variation of acute appendicitis, with the highest incidence from May to October, linear regression showed a significant correlation between the incidence of appendicitis and precipitation (r2=0.28, p-value<0.001). The AI of appendicitis was declining and showed an especially large decline in the year 2020, when the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic began. The overall mortality was 2.3%. A significantly higher mortality rate was found in cases with extreme age (pediatric or geriatric), those with co-morbidities (diabetes, hypertension, dyslipidemia, chronic pulmonary disease, chronic kidney disease), and those with complications, especially generalized peritonitis, sepsis, and acute kidney injury. A decision-tree prediction model suggested that sepsis and renal complication were key nodes determining mortality risk in pediatric and geriatric appendicitis. Conclusion: A mortality risk from appendicitis remains in Thai patients, especially the elderly with co-morbidities and those with generalized peritonitis, sepsis, or renal complications. Early diagnosis and improvement in perioperative care in the extreme age groups might improve the mortality figure.